Effect of different fertilization on the growth and nutrition of azalea (Rhododendron L.) - Zenia Michałojć; Michał Koter (Acta Agrobotanica, 2012)
A study on azalea (Rhododendron L.), 'Kilian' and 'Persil', was conducted in 2009–2010. Plants were grown in pots in the open air, in a peat substrate with a pH of 4.8. The effect of the following fertilization methods was studied: I – traditional fertilization (single fertilizers were applied in 2 rates); II – a slow-release fertilizer (Hortiform pH); III – combined fertilization (¼ of the rate of nutrients was applied in the form of single fertilizers and ¾ in the form of Hortiform pH). The slow-release fertilizer Hortiform pH and combined fertilization were applied once in each study year when filling the pots with growing medium. Fertilizers were applied at the basic rate (D1) and at a twice higher rate (D2). In the first year of cultivation, the study showed no significant effect of fertilization method on shoot length in both azalea cultivars, whereas in the second year the longest shoots were found after application of the slow-release fertilizer Hortiform pH. In both years of the study, significantly longer shoots were found in the cultivar 'Persil' after application of the lower fertilizer rate (D1) than after application of the higher fertilizer rate (D2). On the other hand, the study showed that the fertilizer rate had no effect on shoot length in 'Kilian'. After application of the higher fertilizer rate, a higher content of nitrogen and potassium as well as a lower content of phosphorus, calcium, and magnesium were determined in the leaves of both cultivars. The study found the following percentages to be the optimal nutrient content in azalea leaves: 1.88 – 2.20% N; 1.0 – 1.7% K; and 0.60% – 1.20% Ca, while the phosphorus content of 0.09 – 0.25% and the magnesium content of 0.14 – 0.25% were shown to be the lower limit for optimal plant nutrition. After the end of the growing season, a low content of all nutrients in the medium was found in both study years, irrespective of the applied fertilizer rate and fertilization method.